Body and organ weights, and carcass composition of breeding female White-winged Scoters - Brown, Patrick W; Fredrickson, Leigh H (Wildfowl, 1987)
The weight and carcass composition of 35 breeding female White-winged Scoters Melanitta fusca deglandii from central Saskatchewan and east-central Alberta were determined. Body weights were statistically similar between prelaying and laying, but declined 22.5% (P<0.01) from the end of laying to the end of incubation. Weight loss resulted primarily from absorption of the ovary and oviduct at the end of laying, and the use of fat and protein reserves during incubation. Female White-winged Scoters relied upon their diet to meet most protein and energy requirements during egg laying, whereas stored reserves were needed most to defray energy needs during incubation.